2010
DOI: 10.1111/j.1468-3083.2010.03693.x
|View full text |Cite
|
Sign up to set email alerts
|

Lichen planus and cicatricial conjunctivitis: disease course and response to therapy of 11 patients

Abstract: Lichen planus should be considered in the differential diagnosis of cicatricial conjunctivitis, especially when severe lichen planus is noted at other sites.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
2

Year Published

2011
2011
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(41 citation statements)
references
References 12 publications
0
32
0
2
Order By: Relevance
“…The presence of subepithelial fibrinogen is not necessarily inclusive of any particular eye disease on immunofluorescence analysis, but a fragmented and shaggy subepithelial fibrinogen layer in the conjunctiva is indicative of LP [88, 89]. It is essential to diagnose and treat such disease quickly and efficiently to avoid the dire consequences of blindness [90]. …”
Section: Resultsmentioning
confidence: 99%
“…The presence of subepithelial fibrinogen is not necessarily inclusive of any particular eye disease on immunofluorescence analysis, but a fragmented and shaggy subepithelial fibrinogen layer in the conjunctiva is indicative of LP [88, 89]. It is essential to diagnose and treat such disease quickly and efficiently to avoid the dire consequences of blindness [90]. …”
Section: Resultsmentioning
confidence: 99%
“…Conjunctival involvement with LP is a relatively rare feature of the disease, with 64 cases described in the literature and the vast majority of patients presenting with cicatricial changes. 5,9,10,11,12,13,14,15,16,17,18,19,20,21,22,23,24 Even more uncommonly reported is LP with lacrimal drainage system involvement. Only 11 such patients have been described in various case reports and series 9,10 before Durrani et al (2008) performed a retrospective review of 184 patients with canalicular obstruction.…”
Section: Discussionmentioning
confidence: 99%
“…Conjunctival involvement is rare, and it usually presents as a chronic cicatrizing keratoconjunctivitis in association with other clinical manifestations of LP. [1][2][3][4][5][6][7][8][9][10][11][12] Lichen planus with exclusive involvement of the conjunctiva is exceptional. According to our review criteria, only 6 cases of isolated conjunctival LP have been previously reported.…”
Section: Commentmentioning
confidence: 99%